2005
DOI: 10.1111/j.1439-0329.2005.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro interactions in artificial and wood‐based media between fungi colonizing stumps of Sitka spruce

Abstract: Interspecific interactions between fungi that colonize stumps of Picea sitchensis in Scotland were tested in dual cultures on Norkrans agar, spruce sawdust and in autoclaved blocks cut from roots. Isolates were ranked according to competitive ability on the different media, based on their ability to overgrow competitors or to form deadlock interactions. On the defined medium, Phaeolus schweinitzii was the species most able to overgrow competitors, followed by Stereum sanguinolentum and Heterobasidion annosum; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Although fungal-fungal interactions have been investigated at various levels (e.g. Holmer and Stenlid 1997;Boddy 2000;Woods et al 2005Woods et al , 2006, interactions between stump-colonizing bacteria and fungi have received little attention (Murray and Woodward 2003), and bacterial-bacterial interactions have not been investigated. Variations in the proportions of stump bacteria inhibiting H. annosum with medium used 232…”
mentioning
confidence: 99%
“…Although fungal-fungal interactions have been investigated at various levels (e.g. Holmer and Stenlid 1997;Boddy 2000;Woods et al 2005Woods et al , 2006, interactions between stump-colonizing bacteria and fungi have received little attention (Murray and Woodward 2003), and bacterial-bacterial interactions have not been investigated. Variations in the proportions of stump bacteria inhibiting H. annosum with medium used 232…”
mentioning
confidence: 99%
“…Ganoderma platense, the most aggressive fungus used in this study, showed reduced dry weight loss in dual cultures with E. purpurascens, when the antagonist was inoculated before or after the pathogen. Differences between results obtained from tests carried out on woody substrates and agar substrate have been reported elsewhere (Holmer and Stenlid 1993;Schoeman et al 1994;Woods et al 2005). As differences in nutrients in wood and agar can contribute to this anomaly, extrapolations of findings from synthetic media to natural media are not necessarily valid.…”
Section: Discussionmentioning
confidence: 76%
“…The potential biocontrol activity of several microorganisms against xylophagous hymenomycetes has been demonstrated in in vitro studies (Smith et al 1981;Highley 1989;Sudirman et al 1992;Reaves and Crawford 1994;Schoeman et al 1994;Bruce et al 1995;Highley 1997;Woods et al 2005). We have evaluated the antagonistic ability of Trichoderma harzianum Rifai (Bianchinotti and Lopez 1999) and Epicoccum purpurascens Ehrenb.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Crushing to small fragments however reduces viability dramatically. Burying infected wood blocks besides stumps, dowel inoculation of stems and stumps and colonised sawdust have been tested with so far not satisfying results (Holdenrieder & Craig 1998, Murray & Woodward 2003, Roy et al 2003, Berglund et al 2005, Woods et al 2005.…”
Section: Heterobasidion -Successful Biological Control In Naturementioning
confidence: 99%